2021
DOI: 10.2147/jir.s312167
|View full text |Cite
|
Sign up to set email alerts
|

Astragaloside IV Protects from PM2.5-Induced Lung Injury by Regulating Autophagy via Inhibition of PI3K/Akt/mTOR Signaling in vivo and in vitro

Abstract: Introduction Prolonged exposure to air polluted with airborne fine particulate matter (PM2.5) can increase respiratory disease risk. Astragaloside IV (AS-IV) is one of the main bioactive substances in the traditional Chinese medicinal herb, Astragalus membranaceus Bunge. AS-IV has numerous pharmacological properties; whereas there are few reports on the prevention of PM2.5-induced lung injury by AS-IV through modulation of the autophagic pathway. This study aimed to inve… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
24
1

Year Published

2022
2022
2023
2023

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 44 publications
(26 citation statements)
references
References 79 publications
1
24
1
Order By: Relevance
“…Meanwhile, sham and PM2.5 rats were treated with saline intraperitoneally. The dosage of rosavin and PM2.5 was chosen based on previously reported studies (Pei et al, 2021; Xin et al, 2019).…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…Meanwhile, sham and PM2.5 rats were treated with saline intraperitoneally. The dosage of rosavin and PM2.5 was chosen based on previously reported studies (Pei et al, 2021; Xin et al, 2019).…”
Section: Methodsmentioning
confidence: 99%
“…PM2.5‐induced lung injury is often accompanied by different types of cell death. Our previous studies reported the presence of cell apoptosis and autophagy in lung injury stimulated by PM2.5 exposure (Pei et al, 2021; Wu et al, 2021). It is confirmed that exposure to PM2.5 could cause lung inflammation and oxidative stress by generating reactive oxygen species (ROS) (Long et al, 2020).…”
Section: Introductionmentioning
confidence: 92%
“…Therefore, consumption of nutraceuticals to prevent PM 2.5 -mediated pulmonary damage would be an alternative and attractive option. In regards, several medicinal herbs or those-derived phytochemicals have been suggested to possess pulmonary protective effects against PM 2.5 without serious side effects [ 5 , 6 , 9 , 10 , 11 ].…”
Section: Introductionmentioning
confidence: 99%
“…The mTOR signaling pathway regulates the cell cycle, cell growth, and cell metabolism in physiological and pathological settings; it also plays a crucial role in lung injury (143)(144)(145). In an ALI model, LPS treatment significantly increased the expressions of p-mTOR, p62, and Beclin1, decreased LCII/LCI ratio expression, and enhanced the levels of inflammatory factors in macrophages (123).…”
Section: Induction Of Macrophage Autophagy By Regulating Mammalian Ta...mentioning
confidence: 99%